Do Bony Orbit Dimensions Predict Diel Activity Pattern in Sciurid Rodents?. Issue 10 (17th October 2018) - Smith, Stephanie M.; Angielczyk, Kenneth D.; Schmitz, Lars; Wang, Steve C.
ABSTRACT: Diel activity pattern (DAP) is a key aspect of an animal's ecology, but it is difficult to infer when behavior cannot be directly observed, as in the fossil record. Various anatomical correlates have therefore been used to attempt to classify DAP. Eyeball dimensions are good predictors of DAP because they relate directly to light sensitivity of the eye. Osteological characters, such as scleral ring dimensions, are also reliable proxies, but bony orbit dimensions alone have proven less reliable because soft tissues other than the eyeball can affect orbit size and shape. However, it would be useful if bony orbit dimensions could be used to determine DAP, particularly for mammals, which have no scleral ring, and nonmammalian synapsids, which infrequently preserve scleral rings. We investigated the possibility of predicting DAP in sciurids (Mammalia: Rodentia: Sciuridae) using orbit measurements and other cranial dimensions, and a variety of quantitative methods, including phylogenetic flexible discriminant analysis, classification trees, and logistic regression. The latter two methods do not require a priori assignment of DAP and therefore reflect the situation in a fossil data set. We find that although there are some interfering phylogenetic factors, nocturnal and non‐nocturnal sciurids can be differentiated from one another with over 80% accuracy using all methods investigated here; attempts to differentiate crepuscular animals from nocturnal and diurnal species proved much less successful. Our results indicate that these analyses offer several viable options for predicting DAP in the fossil record, but such analyses should be conducted in a phylogenetic context whenever possible. Anat Rec, 301:1774–1787, 2018. © 2018 Wiley Periodicals, Inc.